STUDI PERKEMBANGAN PASAR TRADISIONAL DAN TOKO MODERN DITINJAU DARI JARAK, AKSESBILITAS, DAN PERILAKU KONSUMEN DI KOTA SURAKARTA - Lestari Hidayati Marfuah; Galing Yudana; Winny Astuti (ARSITEKTURA, 2016)
The development of traditional and modern stores is determined by several factors such as distance, accessibility and consumer behavior. Since the emergence of modern stores in Surakarta, the distance between traditional markets and modern stores are of concern to the government of Surakarta, because the distance is too close location can affect the reduction in income, traders in traditional markets that will impact the sustainability of traditional markets. The second factoris the accessibility factor. The pattern of the spread of modern stores are mostly located in the city center and most are in the residential area of the middle and upper status, whereas traditional markets mostly scattered pad residential areas with medium status. This has an impact on the level of accessibility that is owned by traditional and modern stores, where modern stores willhave a high level of accessibility than traditional markets. The third factor is consumer behavior. Offers and services provided by modern stores make modern store location becomes an alternative place to shop than in the traditional market. The issue of traditional markets will be sought able competitive with modern stores by the City of Surakarta, this study wanted to know how thedevelopment of traditional and modern shops in Surakarta viewed from a distance, accessibility, and consumer behavior. The analytical method used is the analysis techniques skooring and descriptive comparative analysis. The results showed that more modern stores have the opportunity to evolve from the traditional markets. Of these three aspects, aspects of accessibility is a challenge for the traditional market for some traditional markets do not get public transport services. Aspects ofdistances and consumer behavior have the same development category. Keywords:development, traditional markets, modern stores, distance, accessibility, consumer behavior